2019
DOI: 10.2174/1573397114666180809121005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vascular Endothelial Growth Factor in Systemic Sclerosis

Abstract: The pathological hallmarks of Systemic sclerosis (SSc) constitute an inter-related triad of autoimmunity, vasculopathy and tissue remodeling. Many signaling mediators have been implicated in SSc pathology; most focusing on individual components of this pathogenic triad and current treatment paradigms tend to approach management of such as distinct entities. The present review shall examine the role of vascular endothelial growth factor (VEGF) in SSc pathogenesis. We shall outline potential mechanisms whereby d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 116 publications
(170 reference statements)
0
13
0
Order By: Relevance
“…As regards cell-mediated immunity, a relevant role of T lymphocyte responses and pro-inflammatory cytokine aberrant production in the pathogenesis of SSc has been highlighted, with their possible contribution in the modulation of fibrosis and vascular damage [ 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Recent data from our group support the importance of HCMV specific CD8+ T cells, demonstrating a statistically significant association of HCMV-antigen driven CD8+ T cell responses in SSc patients with some of the most relevant disease parameters [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As regards cell-mediated immunity, a relevant role of T lymphocyte responses and pro-inflammatory cytokine aberrant production in the pathogenesis of SSc has been highlighted, with their possible contribution in the modulation of fibrosis and vascular damage [ 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Recent data from our group support the importance of HCMV specific CD8+ T cells, demonstrating a statistically significant association of HCMV-antigen driven CD8+ T cell responses in SSc patients with some of the most relevant disease parameters [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports on the role of VEGF and its inhibitor soluble VEGF receptor-2 (sVEGFR-2), we have also shown that higher concentrations of proangiogenic factors may be found in the tears of patients with scleroderma compared with patients' blood serum and control group [15]. Some previous studies also indicate the major role of VEGF in angiogenesis in systemic sclerosis [32][33][34]. VEGF is involved in many different pathways of angiogenetic processes: initial vasodilation, remodeling of the perivascular matrix, and stimulation of proliferation of endothelial cells [35].…”
Section: Discussionmentioning
confidence: 76%
“…2527 Therapeutic modulation of VEGF-A 165 b is currently being investigated in cancer and angiogenic eye disorders and is being considered to be developed for treating the autoimmune disorder, systemic sclerosis. 28,29 Besides, several reports have described the involvement of VEGF-A in systemic vasculitis, such as GPA (previously known as Wegener’s granulomatosis), 30 giant cell arteritis 31 and Kawasaki disease. 32 Studies have shown the clinical value of VEGF-A in monitoring disease activity in vasculitis, including MPA.…”
Section: Discussionmentioning
confidence: 99%